Improving Quality and Safety through Human Factors Collaborations with Healthcare: The System Engineering Initiative for Patient Safety. (September 2014) - Wetterneck, Tosha; Kelly, Michelle M.; Carayon, Pascale; Sesto, Mary; Tevaarwerk, Amye; Chui, Michelle; Stone, Jamie; Hoonakker, Peter; Musa, Al; Holman, G. Talley; Beasley, John
Multiple reports from the Institute of Medicine and the National Academy of Engineering, (IOM 2001; Reid et al., 2005; Kaplan et al., 2013) have called for the use of human factors engineering (HFE) and systems engineering principles and methods/tools to improve health care delivery. Yet, the integration of engineers into health care settings and the education of clinicians and other health care professionals on human factors and systems engineering principles and methods/tools remain in its infancy. A recent editorial by Xiao and Fairbanks (2011), discusses a small, but growing presence of professionals who are "bilingual" in both human factors and medicine. Indeed, Carayon (2011) identified human factors as an innovation that will require diffusion into healthcare through the use of HFE methods and tools, increasing the health care professional knowledge of HFE, and the hiring HFEs in healthcare organizations. To achieve the goal of integration, there will be many "models" of healthcare – human factors collaborations, from experts working together from their different 'silos' to true bilingualism. SEIPS, the Systems Engineering Initiative for Patient Safety (Carayon et al., 2006), aims to integrate human factors and systems engineering with healthcare disciplines. Our panel of SEIPS-affiliated engineers and healthcare professionals represents many different types of collaborations across this spectrum and their work spans multiple healthcare settings and disciplines, including: ambulatory primary care, inpatient pediatrics, community pharmacy, and oncology.